Indigenous Undergraduates' Use of Supplementary Tutors: Developing Academic Capabilities for Success in Higher Education Studies. Issue 2 (December 2019) - Nakata, Martin; Nakata, Vicky; Day, Andrew; Martin, Gregory; Peachey, Michael
Abstract : This article presents an analysis of statements from Indigenous students in an Australian university that describe how they use supplementary tutors. The analysis provides some evidence that students use tutors for much more than the prescribed remedial purpose to assist with gaps in assumed academic knowledge and skills to prevent subject failures. Students also use tutors to access hidden knowledge and develop capabilities that assist their progress from dependence on assistance to independence in learning. Our analysis has implications for the conceptualisation and management of supplementary tutoring for Indigenous students.